1987
DOI: 10.1136/jcp.40.8.890
|View full text |Cite
|
Sign up to set email alerts
|

"Mucin secreting" and "mucinous" primary thyroid carcinomas: pitfalls in mucin histochemistry applied to thyroid tumours.

Abstract: suMMARY Forty primary carcinomas of the thyroid of different histological types were reviewed and studied histochemically, with the aim of identifying and assessing "mucin secretion". The patterns of extracellular "pure alcianophilia" and "mixed alcianophilia" were noted in 7-5% and about 50% of these tumours, respectively. A critical review of the pitfalls in methods and interpretation of mucin histochemistry-as performed in previously reported cases of "mucin secreting" or "mucinous" primary thyroid tumours-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The presence of stromal mucin, like those found in the present cases, may be produced by stromal fibroblasts or myofibroblasts 11. Extracellular mucin differs from epithelial mucin and is composed of uniformly sulphated acid mucin, which is stained with mucicarmine and Alcian blue but not with PAS, with or without diastase treatment 36. We retrieved 9 cases of primary thyroid neoplasms with extensive extracellular mucin deposition found in the literature 816.…”
Section: Discussionmentioning
confidence: 56%
“…The presence of stromal mucin, like those found in the present cases, may be produced by stromal fibroblasts or myofibroblasts 11. Extracellular mucin differs from epithelial mucin and is composed of uniformly sulphated acid mucin, which is stained with mucicarmine and Alcian blue but not with PAS, with or without diastase treatment 36. We retrieved 9 cases of primary thyroid neoplasms with extensive extracellular mucin deposition found in the literature 816.…”
Section: Discussionmentioning
confidence: 56%
“…Mucin production in thyroid gland is an unusual event but can occur in a wide variety of thyroid lesions (follicular neoplasm, papillary carcinoma, anaplastic and medullary carcinoma) [1,2,6,8,10]. Generally, in these cases, the tumour appears characterized by a pool of mucin, often extracellular and admixed with areas of typical thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Mucinous thyroid tumours are very rare and sometimes can occur in association with a typical thyroid carcinoma (follicular and papillary) but does not represent a true primary thyroid carcinoma [1,2,6,8,10]. This latter is exceptionally rare, with only six cases reported in literature, and histologically are indistinguishable from mucinous carcinoma of others sites [3,5,7,9].…”
Section: Introductionmentioning
confidence: 98%
“…1 The apparent "mucin secretion" is due to histochemical staining of carbohydrate components or breakdown products of thyroglobulin. [13][14][15] Some authors have suggested that the lipid accumulation is due to altered fatty acid metabolism in the tumor cells rather than to metaplasia. 10,16 The natural history of thyroid tumors with clear cell change, however, depends on their basic cytoarchitectural features rather than the presence, amount or type of clear cells.…”
Section: Discussionmentioning
confidence: 99%